Bank Size and Bank Performance During the Covid-19 Pandemic: Evidence from ASEAN - Shindy Dwita Nuansari; Zunairoh; Meme Rukmini; Aulia Annisa Izzati; Ike Cindia; Aji Prasojo; Cantikan dwi (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2026)
ABSTRACT This study examines the impact of COVID-19-related uncertainty on bank performance in ASEAN countries and investigates whether bank size moderates this relationship. While prior studies document the vulnerability of banking sectors during crises, limited empirical evidence explores how bank size shapes resilience in emerging ASEAN markets during the COVID-19 pandemic. This study addresses this gap by employing panel data from commercial banks across ASEAN over the pandemic period. Using panel regression analysis, the results indicate that uncertainty caused by COVID-19 significantly reduces bank performance. However, the negative effect is less pronounced for large banks, suggesting that bank size plays a stabilizing role during systemic shocks. Additional sub-sample analyses across individual countries and between large and small banks confirm the robustness of the findings. This study contributes to the banking and crisis literature by providing empirical evidence on the moderating role of bank size during an unprecedented global disruption. The findings offer important implications for regulators and policymakers in strengthening banking sector resilience against future systemic crises. ABSTRAK Studi ini meneliti dampak ketidakpastian terkait COVID-19 terhadap kinerja bank di negara-negara ASEAN dan menyelidiki apakah ukuran bank memoderasi hubungan ini. Meskipun studi sebelumnya mendokumentasikan kerentanan sektor perbankan selama krisis, bukti empiris yang terbatas mengeksplorasi bagaimana ukuran bank membentuk ketahanan di pasar negara berkembang ASEAN selama pandemi COVID-19. Studi ini mengatasi kesenjangan ini dengan menggunakan data panel dari bank komersial di seluruh ASEAN selama periode pandemi, dengan menggunakan analisis regresi panel. Hasilnya menunjukkan bahwa ketidakpastian yang disebabkan oleh COVID-19 secara signifikan mengurangi kinerja bank. Namun, efek negatifnya kurang terasa untuk bank-bank besar, menunjukkan bahwa ukuran bank memainkan peran penstabil selama guncangan sistemik. Analisis sub-sampel tambahan di masing-masing negara dan antara bank besar dan kecil mengkonfirmasi kekokohan temuan tersebut. Studi ini berkontribusi pada literatur perbankan dan krisis dengan memberikan bukti empiris tentang peran moderasi ukuran bank selama gangguan global yang belum pernah terjadi sebelumnya. Temuan ini menawarkan implikasi penting bagi regulator dan pembuat kebijakan dalam memperkuat ketahanan sektor perbankan terhadap krisis sistemik di masa mendatang.